Isolation, screening and comprehensive characterization of candidate microalgae for biofuel feedstock production and dairy effluent treatment: A sustainable approach - Pandey A.; Srivastava S.; Kumar S. (My University, 2025)
In this study, the indigenous native microalgae were isolated from domestic and dairy effluent (DE) and further screened for DE treatment and lipid accumulation. All the isolated microalgae were examined for their growth adaptability in DE. The growth parameters of 15 isolates were determined and the following six isolates further selected for comprehensive analysis and identified as Desmodesmus sp. ASK01, Chlorella sp. ASK14, Scenedesmus sp. ASK16, Scenedesmus sp. ASK22, Chlorella sp. ASK25 and Chlorella sp. ASK27. The nutrient remediation capacity of six isolates as well as its lipid accumulation potential and biomass composition were determined. The Scenedesmus sp. ASK22 showed the best combined results and promising strain for the DE treatment and biofuel production. Biomass composition of Scenedesmus sp. ASK22 showed an oil accumulation of 30.7% (w/w) and biomass yield 1.22 g L−1. The fatty acid methyl ester (FAME) mainly composed of C15:0, C16:0, C18:0, C18:1 and C18:3. © 2019 Elsevier Ltd